The Effect of Water Vapor and Solar Zenith Angle on Oceanic Diurnal Warming - Andrew Harris; Gary Wick; Sandra Castro (Geophysical Research Letters)
Abstract Oceanic diurnal warm layers have been extensively studied over the years due to their important role in a variety of geophysical disciplines. Much of this research has been dedicated to the development of predictive models of varying complexity to calculate the spatiotemporal magnitude of the effect. This manuscript presents results which show that significant variability can be accounted for by addressing the combined impacts of atmospheric water vapor and solar zenith angle on both the spectral distribution of insolation energy at the water surface and its subsequent absorption within the water column. Comparisons with satellite‐observed diurnal amplitudes on the basin‐scale show that the new scheme provides notable improvements over one with a fixed insolation parameterization. One implication is that addressing the heat source term within the water column is a key first step when developing and tuning models of the diurnal layer.